2022
DOI: 10.1021/acsabm.2c00411
|View full text |Cite
|
Sign up to set email alerts
|

Role of Reactive Oxygen Species in Aging and Age-Related Diseases: A Review

Abstract: Research on the role of reactive oxygen species (ROS) in the aging process has advanced significantly over the last two decades. In light of recent findings, ROS takes part in the aging process of cells along with contributing to various physiological signaling pathways. Antioxidants being cells' natural defense mechanism against ROS-mediated alteration, play an imperative role to maintain intracellular ROS homeostasis. Although the complete understanding of the ROS regulated aging process is yet to be fully c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 350 publications
0
36
1
Order By: Relevance
“…Genes that compose Complex I and Complex III of the electron transport chain (ETC) were significantly enriched for positive selection. These complexes are hypothesized to be the primary source of reactive oxygen species production in the ETC, where a severe abundance of reactive oxygen species has been linked to several age-related diseases 51,52 . In contrast to the germline, the mt-genome is predominantly shaped by positive selection in somatic tissues; yet, the effects that these mutations have at the mitochondrial and cellular level along with the advantages these mutations confer remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Genes that compose Complex I and Complex III of the electron transport chain (ETC) were significantly enriched for positive selection. These complexes are hypothesized to be the primary source of reactive oxygen species production in the ETC, where a severe abundance of reactive oxygen species has been linked to several age-related diseases 51,52 . In contrast to the germline, the mt-genome is predominantly shaped by positive selection in somatic tissues; yet, the effects that these mutations have at the mitochondrial and cellular level along with the advantages these mutations confer remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic OVA was disseminated and stabilized in a hydrophobic IPM solution in ILNDFs utilizing LBIL-([EDMPC][Lin]) and cationic/anionic/non-ionic conventional surfactants at a 1:1 w/w ratio ( Figure 1 A). DLS was used to measure the particle size (n/z) and PDI of the ILNDFs (summarized in Table 1 ), and the particle size was approximately or below 500 nm in all formulations ( Figure S2i ), which is suitable for TDDSs [ 4 , 29 , 30 ]. The CLSM observation confirmed that the FITC-OVA nanoparticles moved freely in the IPM, and the particle size agreed well with the DLS observation ( Figure S2i,ii ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ROS production derives from a series of ways, and each is influenced by many factors, although the oxidative stress pathway is the main one. 48 In addition, it is reported that unchanged excretion of urinary 8-OH-dG at increased oxidative burden does not rule out the possibilities of a decreased repair capacity and accumulation of 8-OH-dG in DNA. 49,50 To clarify this issue, more research studies should be conducted to obtain more comprehensive and accurate data to improve the understanding.…”
Section: ■ Results and Discussionmentioning
confidence: 99%